(untitled) (Modern American Journal of Engineering, Technology, and Innovation, 2026)
This article analyses the natural-climatic, constructive, urban-planning and operational factors affecting the energy efficiency of low-rise residential buildings under the climatic conditions of Fergana Region. According to climatic data, the average annual temperature in Fergana city is about 15.3 °C and the annual precipitation is approximately 308 mm. The hot and dry summer, together with the relatively short but cold winter period, creates a dual energy load in buildings: heating demand in winter and cooling or overheating risk in summer. The study evaluates heat losses, heating degree-days and the relative contribution of building-envelope elements for a sample 120 m² low-rise dwelling. The calculations show that integrated improvement of external walls, roof, ground floor, windows and infiltration parameters may reduce the calculated annual space-heating demand from 188.0 to 87.9 kWh/m²·year. The results confirm the need to design energy-saving measures for the housing stock of Fergana Region on the basis of local climatic characteristics.